Contracting with Nonfinancial Stakeholders and Corporate Capital Structure: The Case of Product Warranties - Kale, Jayant R.; Meneghetti, Costanza; Shahrur, Husayn (Journal of Financial and Quantitative Analysis, 2013)
Abstract We investigate the relation between a firm’s product warranty level and its leverage. We find that leverage relates negatively to the warranty level and that this relation is robust to controls for endogeneity and self-selection into offering warranties. The negative warranty-leverage relation obtains only in the subsample of firms in the manufacturing industries. We also show that firms with warranties have the lowest debt levels, firms without warranties but operating in industries where other firms offer warranties on average carry higher debt, and firms in industries where no firm offers a warranty have the highest debt levels.